Optimizing the Role of Tourism Villages in Community Economic Development : (Study in Sungai Kakap Village, Sungai Kakap Subdistrict, Kubu Raya Regency) - Tiza Yaniza; Ismail Marzuki; Tia Savitria (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
This research is entitled Optimizing the Role of Tourism Villages in Community Economic Development (Study in Sungai Kakap Village, Sungai Kakap Subdistrict, Kubu Raya Regency) with the aim of knowing how the role of Sungai Kakap Tourism Village in the economic development of the local community and raised three problems, first what factors influence in optimizing the development of Sungai Kakap Tourism Village, Sungai Kakap Subdistrict. second, how is the strategy to optimize the development of Sungai Kakap Tourism Village, Sungai Kakap Subdistrict optimally and third, how is the impact of the village in improving the economy for the local community. This type of research is a qualitative approach, the method used is the method of juridical sociological approach, the population in this study are business actors around the tourist village of Sungai Kakap sub-district. Data collection techniques through observation, interviews, and documentation techniques. The results of this study indicate that the tourist village in Sungai Kakap sub-district has received less attention from the government so that it has not been so optimal in improving the economy of the local community. The strategy to optimize the development of Sungai Kakap Tourism Village is the involvement of the local government to promote the tourism village, so that it will have a good impact on the local community in improving the economy.